Determinants of energy efficiency in the Dutch dairy sector: dilemmas for sustainability. (15th April 2021) - Moerkerken, Albert; Duijndam, Sem; Blasch, Julia; van Beukering, Pieter; Smit, Arnoud
Abstract: Since the European Energy Efficiency Directive, a lot of attention has been paid to energy saving measures, including how to overcome the barriers for implementation. This paper addresses the dilemmas of the Dutch dairy sector, where farms are getting bigger and mechanization is increasing, while at the same time the sector is aiming for improved energy efficiency and sustainability. With an online tool which systematically recorded the energy performance of dairy farmers, a unique dataset on farm energy use with more than 25, 000 observations over the years 2015–2018 was obtained. This allows for a robust analysis of the determinants of energy efficiency in the sector, using panel data analyses. The results of this study reveal three major trends. First, the on-farm use of solar panels proves to be the most significant determinant for reducing non-renewable energy use. Second, gains in energy efficiency triggered by government policies are countervailed by the continuous trend of mechanization, with especially automatic milking systems causing lower energy efficiency. Third, the increasing economies of scale in milk production substantially improve per-unit energy efficiency. However, the increased need for mechanization related to higher on-farm production can cancel out this economies-of-scale effect. These findings add important new insights to the literature on cleaner production in farms and have important policy implications. Strategies for more energy-efficient farming should entail two directions for innovation: first, the stimulation of more energy efficient automatic milking systems, and second, the stimulation of solar energy production on farms including a better on-farm utilization of solar electricity. Graphical abstract: Image 1 Highlights: The drivers for energy efficiency were examined based on 25, 000 dairy-farm records. The best method to increase non-renewable energy efficiency is applying solar energy. Production increase improves energy efficiency but usually also increases GHG emissions. Having an automatic milking system (AMS) decreases the on-farm energy efficiency. The effects of energy saving measures are overruled by these three trends.